On Some Punctuation Issues of Modern Eastern Armenian Modal Words - SARGSYAN, LIANA (Bulletin of Yerevan University B: Philology, 2021)
In Modern Eastern Armenian, the punctuation of some grammatical tags raises confusion. Over time, some contradictions appear in the rules and structural usage of punctuation. There is a part of a quotation or parallel punctuation threads, which is contrary to the punctuation rules. This article will detail the rules and threads of such contradictions and obstacles to the realization of the textbooks and instructional materials in Modern Eastern Armenian. Guided by this modern punctuation dilemma, as well as inter-linguistically attempt tojustify and correct punctuation structures freely.